2009
DOI: 10.1074/jbc.m109.052910
|View full text |Cite
|
Sign up to set email alerts
|

A Double Tyrosine Motif in the Cardiac Sodium Channel Domain III-IV Linker Couples Calcium-dependent Calmodulin Binding to Inactivation Gating

Abstract: Voltage-gated sodium channels maintain the electrical cadence and stability of neurons and muscle cells by selectively controlling the transmembrane passage of their namesake ion. The degree to which these channels contribute to cellular excitability can be managed therapeutically or fine-tuned by endogenous ligands. Intracellular calcium, for instance, modulates sodium channel inactivation, the process by which sodium conductance is negatively regulated. We explored the molecular basis for this effect by inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 37 publications
2
69
3
Order By: Relevance
“…The DIII-IV linker residue M1498 has a large contact area with CaM with 107 Å 2 out of 118 Å 2 buried (Fig. 1B), suggesting it could contribute to Ca 2+ /CaM binding and regulation of Na V s. Previous ITC experiments have shown that the interaction requires Ca 2+ and is supported preferentially by the C lobe (K d 19 μM versus ∼600 μM for the N lobe) (9). In addition, competition experiments whereby the C lobe is already bound to the DIII-IV linker show that the residual affinity of the N lobe is undetectable (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The DIII-IV linker residue M1498 has a large contact area with CaM with 107 Å 2 out of 118 Å 2 buried (Fig. 1B), suggesting it could contribute to Ca 2+ /CaM binding and regulation of Na V s. Previous ITC experiments have shown that the interaction requires Ca 2+ and is supported preferentially by the C lobe (K d 19 μM versus ∼600 μM for the N lobe) (9). In addition, competition experiments whereby the C lobe is already bound to the DIII-IV linker show that the residual affinity of the N lobe is undetectable (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2B; K d 0.35 μM vs. 2.98 μM for WT). The energetic impact of single Y1494A or Y1495A mutations on the WT or 1491-1522 constructs results in enthalpic penalties of 5 kcal/mol and 3 kcal/mol, respectively, which were matched with an equal gain in entropy, leaving the overall affinities unchanged (Table S2) (9). Given the identical energetic signature and enthalpy-entropy compensations, the interactions with Ca 2+ /CaM are likely to be the same in 1491-1522 and full-length DIII-IV linkers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations